Transcriptomic analysis for the gamma-ray-induced sweetpotato mutants with altered stem growth pattern - Lee, Hyeong-Un; Shim, Sangrea; Chung, Mi Nam; Lee, Taeyoung; Park, Won; Kim, Tae Hwa; Lee, Kyo Hwui; Woo, Koan Sik; Nam, Sang-Sik; Kim, Moon Young; Lee, Suk-Ha (Frontiers in Genetics, 2024)
Introduction: Sweetpotato faces breeding challenges due to physiological and genomic issues. Gamma radiation is a novel approach for inducing genetic variation in crops. We analyzed the transcriptomic changes in gamma ray-induced sweetpotato mutants with altered stem development with those in the wild-type 'Tongchaeru' cultivar. Methods: RNA sequencing analyses were performed to identify changes in the expression of genes related to stem development. Results: Transcriptomic analysis identified 8,931 up-regulated and 6,901 down-regulated genes, including the up-regulation of the auxin-responsive SMALL AUXIN UP RNA (SAUR) and three PHYTOCHROME INTERACTING FACTOR 4 (PIF4) genes. PIF4 is crucial for regulating the expression of early auxin-responsive SAUR genes and stem growth in Arabidopsis thaliana. In the mutant, several genes related to stem elongation, including PIF4 and those involved in various signaling pathways such as auxin and gibberellin, were up-regulated. Discussion: Our results suggest that gamma ray-induced mutations influence auxin-dependent stem development by modulating a complex regulatory network involving the expression of PIF4 and SAUR genes, and other signaling pathways such as gibberellin and ethylene signaling genes. This study enhances our understanding of the regulatory mechanisms underlying stem growth in sweetpotato, providing valuable insights for genomics-assisted breeding efforts.